Facts about Fructose - Wendy J. Dahl; Lauren Foster; Russell J. Owen (EDIS, 2014)
Fructose is a simple sugar found in many foods. Common table sugar is made of equal amounts fructose and glucose. Similarly, high-fructose corn syrup, commonly used to sweeten foods, contains a mixture of fructose and glucose. Fructose is sweeter than glucose, and for this reason it has been used in many sweetened foods. This revised 2-page fact sheet was written by Wendy Dahl, Lauren Foster, and Russel Owen, and published by the UF Department of Food Science and Human Nutrition, June 2013.